Kesatuan dan Harmoni dalam Masyarakat Jawa - Rosmaria Syafariyah Widjajanti (Refleksi: Jurnal Kajian Agama dan Filsafat, 2006)
In societal life, problems arising from interaction processes are inevitable. Various interests flowing through diverse cultures within society do not always end in conflict and violence. There is harmony and unity that can emerge from social interactions. This is evident in Javanese society, which emphasizes the principles of harmony in its social relations. In Javanese society, the relationship between humans and God is seen as a unity and harmony. This harmonious relationship serves as a model for the relationship between humans and society. Efforts to achieve harmony are made by maintaining order within society. Thus, the unity of the individual and society implies the existence of order. Threats to this harmony include personal ambition and desires. Someone in society who is too ambitious and prioritizes personal desires is considered a threat to social order.